Metode Demonstrasi Menggunakan Model Motor Bakar untuk Meningkatkan Aktivitas dan Hasil Belajar Proses Mesin Konversi Energi bagi Siswa Kelas X TKR 2 SMK Negeri 2 Kebumen - Haryoko, Haryoko (LP3 Universitas Negeri Semarang, 2016)
The purpose of this result is to improve the activity and learning outcomes in the basic competence learning the process of energy conversion machine by applying the demonstration method using a motor fuel model for students of class X TKR 2 Kebumen Vocation High School 2nd semester school year 2015/2016. The procedure of the research is carried out through two cycles, each cycle consisting of four steps, namely: (1) planning, (2) the implementation, (3) observations, and (4) evaluation process with reflection. The results of the empirical research proves that implementation method using demonstation method using a motor fuel model, the liveliness of very active students category increase from the initial condition there are 3 students (8%) become 8 students (13,9%) in cycle I, become 7 students (19,4%) in cycle II, and in cycle III increase to 9 students (25%). The liveliness of active students category increase from the initial conditions there are 16 students (44%) become the 21 students (58,3%) in cycle I, increase to 25 students (69,4%) in cycle II, and from cycle II to cycle III there is no improvements. Yhe number of students who learning comprehensively is 36 students in initial conditions 31% with an average value 65,7 increase in cycle I become 44% with an average value 69,6 increase in cycle become 78% with an average value 74,1. From cycle II to cycle III number of students who learning comprehensively increase to 89% with an average value 76,0.